The Role of Global Civil Society at the Local Level in Climate Change Mitigation: A Case Study of Earth Hour’s Activities in Malang - Rijal, Najamuddin Khairur (Global: Jurnal Politik Internasional, 2020)
This study examines the role of global civil society at the local level in climate change mitigation. Climate change issue is one of the global issues that is responded at the local level, as the impact of the problem concerns the universal livelihood of the world’s population. This study focuses on Earth Hour’s activities in the Malang region as a part of a global civil society. This research uses global civil society and its role in environmental governance as the analytical framework. The data are collected through documentation studies and interviews. The results show that Earth Hour Malang’s activities have three important roles in climate change mitigation efforts, namely information-based role, providing policy inputs to the government, and performing operational functions.